Breaking the Chain of the Nativist/Owner Metaphor in World Englishes - Keith Lloyd (Cranmore Publishing, 2020)
Since the inception of Kachru's (1976) "three circles" model of World Englishes, the field has struggled with the relation between British and American Englishes and second and third circle innovations such as Hinglish, Singlish, Japlish, etc. Despite efforts from many scholars to approach all Englishes as relatively equal, "native speaker/standard" forms of British and American English continue to be the benchmarks of proficiency, and standard English competency an avenue to economic and political advantage, a situation Phillipson labels "linguistic imperialism." Challenging this imperialistic dichotomy is necessary if we are to find ways to "decolonize" (Bhatt, 2001, p. 544) the study, teaching, and perception of World Englishes. This article uniquely applies Conceptual Metaphorical Analysis of the native speaker/owner metaphor that sustains this situation, interpreting it through what Lakoff and Johnson (1980) refer to as metaphorical "entailments" (Metaphors we live by, p. 9), associations that enable the dominant metaphor. This article illustrates how we can break this chain of entailments by displacing the fictional standard of the native speaker, deconstructing the notion that English as an object one can own, and exposing the mistaken belief that there is or ever has been such a thing as "standard English." The final section offers some alternatives to the native speaker/owner metaphor that open the possibility that English belongs to both no one and everyone.